Scoping Review Kejadian Luar Biasa Hepatittis A di Indonesia Tahun 1998-2018 - Rilla Venia Lalu; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Scoping review hepatitis a outbreaks in Indonesia: 1998-2018Purpose: The purpose of this study was to determine the distribution of cases and risk factors of outbreaks of hepatitis A in Indonesia during 1998-2018. Method: Scoping review conducted on electronic data from journal articles as well as published and unpublished reports (grey literature) from 1998-2018. Online databases such as Google Scholar and Pubmed. Grey literature is obtained from the library and from the unpublished report document results obtained from the University of Indonesia (UI) and University of Gadjah Mada (UGM). In the process of select and data extraction aided by 2 reviewers. Results: Outbreaks of hepatitis A were reported to occur in 47 incidents during 1998-2018 with the outbreak area mostly occurring in East Java, West Java and Central Java. Men are more at risk (63.4%) of hepatitis A than women and 15-34 years is the age most at risk of hepatitis A. The hepatitis A outbreak area is the most at school / campus with proportion (41.5%), cottage boarding schools (31.7%) and in residential or community environments (24.4%) The risk factors that most contribute to outbreaks of hepatitis A at school/campus and in the community are the habit of not washing hands with soap before eating and consuming foods that are not hygienic. While in boarding schools is the use of shared eating/drinking tools. Conclusion: School age and young adults are the age groups most at risk for hepatitis A. Unhygienic individual behavior (not washing hands before eating) is a major contributing factor to the transmission of hepatitis A.